Effect of Gender, Toe Extension Position, and Plantar Fasciitis on Plantar Fascia Thickness. (April 2019) - Granado, Michael J.; Lohman, Everett B.; Daher, Noha S.; Gordon, Keith E.
Background: Ultrasound is a widely used diagnostic tool for patients with plantar fasciitis. However, the lack of standardization during the measurement for plantar fascia thickness has made it challenging to understand the etiology of plantar fasciitis, as well as identify risk factors, such as gender. The purpose of this study was to investigate gender differences regarding plantar fascia thickness while controlling for metatarsophalangeal (MTP) joint position in the healthy and those with unilateral plantar fasciitis. Methods: Forty participants (20 with unilateral plantar fasciitis and 20 controls) with plantar fascia thickness (mean age, 44.8 ± 12.2 years) participated in this study. The majority were females (n = 26, 65%). Plantar fascia thickness was measured via ultrasound 3 times at 3 different MTP joint positions: (1) at rest, (2) at 30 degrees of extension, and (3) at maximal extension. Results: When comparing gender differences, the males in the plantar fasciitis group had a significantly thicker plantar fascia than the females ( P = .048, η 2 = 2.35). However, no significant differences were observed between healthy males and females. The males with unilateral plantar fasciitis also had significantly thicker asymptomatic plantar fasciae collectively compared with controls ( P < .05), whereas females with unilateral plantar fasciitis had a similar but not significant change. Conclusion: It appears that healthy males and females have similar plantar fascia thickness. However, as plantar fasciitis develops, males tend to develop thicker plantar fasciae than their female counterparts, which could have future treatment implications. Level of Evidence: Level III, case-control comparative study.